The political economy of food and nutrition policies - Pinstrup-Andersen, Per (International Food Policy Research Institute, 1993)
Per Pinstrup-Andersen brings together a group of distinguished authorities to improve the understanding of how nutrition policies are formulated within larger political and economic contexts and how public-sector agencies behave with regard to food and nutrition. ..This book was conceived on the notion that an enhanced qualitative understanding of the political economy issues and relationships would assist in further improving the political economy approach to policy analysis, advice, design, and implementation." (Excerpts from text)